Efficacy and safety of once-weekly insulin versus once-daily insulin in patients with type 1 and type 2 diabetes mellitus: an updated meta-analysis of randomized controlled trials - Xue, Mei; Shen, Pan; Tang, Jun; Deng, Xuan; Dai, Zhe (Frontiers in Endocrinology, 2024)
Background: This meta-analysis was performed to obtain a comprehensive overview of differences between once-weekly basal insulin (including icodec and basal insulin Fc) with once-daily basal insulin (including glargine and degludec) in patients with type 1 and type 2 diabetes mellitus. Methods: PubMed, EMBASE, and Cochrane Library were systematically searched for eligible studies up to January 2, 2024. Results: A total of 12 studies were included comprising 5895 patients, 3104 (52.7%) using once-weekly insulin and 2791 (47.3%) using once-daily insulin. In the pooled data, glycated hemoglobin (HbA1c) change from baseline (MD -0.11%; 95% CI -0.20 to -0.01%) and the odds of achieving an end-of-trial HbA1c <7% (OR 1.41, 95% CI 1.13, 1.77) demonstrated a significantly well glycemic control in the once-weekly insulin group, especially in insulin-naïve type 2 diabetes or people using icodec. Body weight increase for once-weekly insulin was 0.43kg compared to controls (95% CI 0.09 to 0.76kg). In addition, once-weekly insulin was correlated with a higher risk of level 1 hypoglycemia (OR 1.42, 95% CI 1.26 to 1.6). There was no significant difference in fasting plasma glucose (MD 2.46 mg/dL; 95% CI -2.60 to 7.52 mg/dL), time in range (MD 2.03%; 95% CI -0.50 to 4.56%), and level 2 or 3 hypoglycemic events (OR 1.19; 95% CI 0.93 to 1.53). Conclusions: Once-weekly basal insulin is safe and effective in modestly reducing HbA1c with similar level 2 or 3 hypoglycemic events compared to once-daily insulin, although the risk of level 1 hypoglycemia and weight gain was slightly increased.